2018
DOI: 10.3390/molecules24010132
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Effects of Acanthopanax senticosus HARMS Occur via Regulation of Autonomic Function and Activate Hippocampal BDNF–TrkB Signaling

Abstract: Mental stress, such as anxiety and conflict, causes physiological changes, such as changes in autonomic nervous activity and gastric ulcers. In addition, stress induces glucocorticoids and changes the hippocampal brain-derived neurotrophic factor (BDNF) expression levels. We previously reported that Acanthopanax senticosus HARM (ASH) prevents stress-induced gastric ulcers. Thus, we investigated the potential anxiolytic effect and influence of ASH on the hippocampus BDNF-related protein in male Sprague-Dawley r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
(71 reference statements)
1
26
0
Order By: Relevance
“…Therefore, ASH and Mix show partial anxiolytic effects similar to CLO in OFT. In a previous study, we demonstrated the anxiolytic effect of ASH in the IEBW test 16 . ASH extract administration extended staying time in the open arm and ameliorated the elevation of SNS activity and suppression of PNS activity in the IEBW test.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Therefore, ASH and Mix show partial anxiolytic effects similar to CLO in OFT. In a previous study, we demonstrated the anxiolytic effect of ASH in the IEBW test 16 . ASH extract administration extended staying time in the open arm and ameliorated the elevation of SNS activity and suppression of PNS activity in the IEBW test.…”
Section: Discussionmentioning
confidence: 78%
“…After 1-week acclimatization, rats were implanted the telemeter in the abdomen (see Supplementary Materials and Methods 1.1 for details). Based on the test food consumption in our previous study of the ASH extract 16 , we determined the dose of each test item (CHA[Sigma-Aldrich, C3878], 40 mg/kg; SYG, 32 mg/kg; Mix, a mixture of CHA and SYG) dissolved in distilled water. CLO (SEPAZON, Alfresa Pharma Co., Osaka, Japan) was administered at a dose of 0.2 mg/kg in 1 mL of distilled water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1980s, AS was shown to enhance the immune-modulatory effect clinically. Scientists demonstrated that an ethanolic AS preparation caused a drastic increase in the absolute number of immunecompromised cells with a noticeable effect on T lymphocytes (predominantly helper cells) as well as cytotoxic and natural killer cells in healthy volunteers (Miyazaki et al, 2018;Zhou et al, 2018a;Zhou et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%